Определение угловых координат беспилотных летательных аппаратов - Неменко, Е. С. (ХНУРЕ, 2020)
Unmanned aerial vehicle (UAV) may have varying degrees of autonomy from remotely controlled to fully automatic, and also vary in design, purpose and many other parameters. The main advantage of UAV is the significantly lower cost of their creation and operation (provided that the tasks are equally effective). The disadvantage of unmanned aerial vehicle is the vulnerability of remote-control systems, which is especially important for military UAV. Can solve reconnaissance tasks (today this is their main purpose), can be used to strike ground and sea targets, intercept air targets, perform radio interference, control fire and target targets, relay messages and data and deliver cargo.
Keywords: определение угловых координат; БПЛА